Geometric morphometric analysis of the pharyngeal airway during treatment of Class III malocclusion - Kaygisiz, Emine; Ocakoglu, Gökhan; Kurnaz, Merve; Yüksel, Sema; Tortop, Tuba (American journal of orthodontics and dentofacial orthopedics, 2022)
The pharyngeal airway is important during diagnosis and treatment planning in orthodontics. This study aimed to compare the changes in the shape of the pharyngeal airway in patients with Class III malocclusion treated with a facemask (FM) with a removable maxillary appliance and modified tandem traction bow appliance (MTTBA). This study consisted of pretreatment and posttreatment lateral cephalograms of 35 subjects with skeletal and dental Class III malocclusion. In the first group, 20 patients (12 males, 8 females; mean age, 10.2 years) were treated with MTTBA. The mean treatment time was 12 months. In the second group, 15 patients (10 males, 5 females; mean age, 10.3 years) were treated with FM. The mean treatment time was 11.7 months. Nineteen pharyngeal landmarks were considered from the image corresponding to the midsagittal plane and marked using tpsDig software (version 2.04; Stony Brook, NY). Pharyngeal airway shape difference between the groups was assessed by performing a Generalized Procrustes analysis. The shape deformation of the pharyngeal airway from the pre- to posttreatment periods was evaluated using the thin-plate spline method. There were no differences between MTTBA and FM groups according to airway shape for pretreatment and posttreatment periods. However, there were some deformities using the enlargement of the nasopharyngeal area in the FM group and oropharyngeal area in the MTTBA group according to pretreatment periods. There were no differences between the groups according to the mean pharyngeal airway shapes when the posttreatment periods of the FM and MTTBA groups were examined. •Morphometric analysis is a new way of evaluating pharyngeal airway.•Pharyngeal airway shape changes were evaluated in patients treated for Class III malocclusion.•Enlargement of the superior pharyngeal area was found in the facemask group.•Enlargement of the superior oropharyngeal area was observed in the MTTBA group.•No differences were found in the mean pharyngeal airway shapes between the groups.